Manejo por ambiente: atributos de solo e desempenho de cultivares de soja - Corassa, Geomar Mateus (2015)
The crop productivity mapping is an important precision farming tool enabling more efficient spatial management of agricultural areas. In this sense, the objective of this work was to identify and analyze zones with different grain yield potential (Article I), check the association of chemical and physical properties of the soil with the yield zones (Article II), and evaluate the agronomic performance of six soybean cultivars in zones with different grain yield potential. For the definition of the yield zones were used three harvest maps of different cultures in two experimental areas. The maps were filtered and the defined zones and grouped from the overlap of crops (Article I). The search for chemical and physical atributes of the soil associated with grain yield was performed by systematic soil collection, according to grain yield zones (high, medium and low) (Article II), and analyzed 80 chemical variables and 33 physical variables by using descriptive statistics and ranked by principal component analysis (PCA). The agronomic performance of soybean cultivars in different grain yield zones (Article III) was evaluate in two agricultural areas, being allocated experiments in the random block design in factorial 3x6, with three grain yield zones (high, medium and low) and six soybean cultivars (BMX Ativa RR, Fundacep 65 RR, FPS Urano RR, FPS Júpiter RR, Nidera 5909 RG and BMX Força RR), with three replications. The results showed that the use of a historical series of harvest maps is an efficient tool to characterize sites with different grain yield potential, in addition to serving as a base for improving the spatial management of agricultural areas. The systematic soil sampling was able to reveal explanatory variables for grain yield, and the order for intervention in chemical attributes in the área is: Liming, phosphate fertilization and potassium fertilization. The presence of attributes of difficult management in the short time (organic matter and clay) associated with grain yield potential suggests the crop management in the management zones. The yield zones influenced the grain yield of soybean cultivars, and the cultivar BMX Força RR presented its highest grain yield in the ZB, whereas NA 5909 RG was more productive in the ZA and ZM. The cultivar BMX Ativa RR was on average more productive and more stable. The results indicate that the positioning of soybean cultivars in accordance with management zones is a important strategy for the precision agriculture and characterized as a new concept of the ―multi-cultivars‖ sowing.